The Tunable White‐Light and Multicolor Emission in An Electrodeposited Thin Film of Mixed Lanthanide Coordination Polymers. Issue 11 (30th June 2015) - Liu, Huiping; Chu, Tianshu; Rao, Zilong; Wang, Shuoyu; Yang, Yangyi; Wong, Wing‐Tak
Abstract : A white‐light‐emitting lanthanide coordination polymer thin film is fabricated for the first time by electrodeposition based on a novel hexanuclear lanthanide cluster, in which, Tb 3+ generates green emission and enhances the Eu 3+ ‐centered red emission through energy transfer process; the ligand generates blue emission. Notably, white‐light emission with CIE coordinates of (0.33, 0.34) is obtained by balancing Tb 3+ /Eu 3+ ratio and excitation wavelength.